Characterization and Thermal Behavior of Hydroxyapatite Prepared by Precipitation - Šimková, Lenka; Šulcová, Petra (Springer, 2019)
The aim of this study was to find appropriate precipitation conditions (Ca/P ratio, pH and precipitation rate) for the synthesis of hydroxyapatite (HAP; Ca-10(PO4)(6)(OH)(2)) and to determine the effect of precipitation conditions on its thermal behavior. Hydroxyapatite was synthesized by precipitation. Three ratios of Ca/P (1; 1.67; 3) were selected for the synthesis, then pH 7 and 12 was selected, and the ammonium dihydrogen phosphate precipitation rate was set to 2 mL min(-1). The prepared powders were studied from the standpoint of particle size distribution, crystal size and morphology (optical microscope, scanning electron microscope), phase composition (X-ray diffraction analysis) and thermal stability in relation to the Ca/P ratio.
Charakterizace a tepelné chování hydroxyapatitu připraveného srážením
Keywords: Hydroxyapatite; Precipitation; Ca/P ratio; XRD; SEM; Simultaneous DTA-TG analysis; Hydroxyapatit; srážení; poměr Ca/P; XRD; SEM; DTA-TG